Formulasi Granul Effervescent Ekstrak Daun Leilem (Clerodendrum minahassae L) - Palobo, Fabiola N; Yamlean, Paulina V. Y.; Yudistira, Adithya (PHARMACON, 2012)
Leilem Leaves had a bitter taste, but it is believed as antioxidant. This research aims to find way formaking a formulation of effervescent granules from Leilem leaves extract wich is demand thestandards for effervescent granules. The extracts resulted from soxhletasi method with 95% ethanol(1:5), and the formula based from 7% extract, citric acid 16.2%, 25.2% tartaric acid, lemon essence2%, 0.5% CMC, and food coloring. Effervescent granules from Leilem leaves are prepared by drygranulation method. Results of manufacturing effervescent granules was tested by physical stuff, andthen compared with the literature, the test results showed effervescent granules have a regularlyshape, with orange-scented, had a 4.35% value of LOD, the pour volume is 150g/183mL with 1.09%volume of shrinkage, the test flow capacity is 30.650, and able to complete the test of dispersion timefor 1 minute 9 seconds. Based on these results it can be concluded that the extract of Leilem leavescan be made an effervescent granules by dry granulation method, and has a good quality because itwas demand the standards test of good granules.Key word: Clerodendrum minahassae L, Ekstract, Formulation, Effervescent